2015 Section on Pediatrics Knowledge Translation Lecture: Pediatric Vestibular-Related Impairments. Issue 1 (2016) - Rine, Rose Marie; Dannenbaum, Elizabeth; Szabo, Joanne
Abstract : Key Points: Until recently, the incidence and effect of vestibular system impairments in children has been grossly underidentified and thus not addressed. Because of incidence reports (approximately 10% of the US population younger than 21 years) and evidence of the efficacy of evaluation methods and interventions, researchers and clinicians are focusing on development of optimal interventions to enhance function, thus minimizing the negative effect of vestibular hypofunction on reading, motor development, and postural control. However, research progress has been slow. How can clinicians and researchers collaborate so that (1) vestibular deficits and related impairments can be identified in children, and (2) optimal interventions can be identified and implemented so that children with peripheral and/or central vestibular dysfunction can benefit? Summary: Our participation in knowledge translation is presented, to include discussion of possible barriers, challenges, and opportunities for facilitating collaboration and joint efforts of clinical and research practice. Abstract : The authors illustrate how clinicians and researchers can collaborate to identify vestibular deficits and related impairments and optimal interventions so that children with peripheral and/or central vestibular dysfunction can benefit.